Supplementary far-red light enhances the quality and root development of double-root-cutting grafted watermelon seedlings - Wu, Cuinan; Wang, Yaya; Cao, Kai; Bao, Encai; Ding, Haiyan; Zhou, Xiaoting; Dong, Yifan; Xu, Shipu; Wu, Xue (Frontiers in Plant Science, 2025)
IntroductionThe regeneration of roots is crucial for the survival and healthy development of double-root-cutting (DRC) grafted watermelon seedlings. However, methods to effectively enhance root regeneration in the rootstock of DRC grafted watermelons remain unclear.MethodsIn this study, supplementary far-red (FR) light was applied to DRC grafted watermelon seedlings to evaluate its impact on seedling growth and rooting, using dark (CK) as the control.Results and discussionsIt was discovered that supplementary FR light substantially promoted root development in the rootstock, reducing the time required for root regeneration and boosting root biomass. Transcriptome profiling indicated that genes associated with sugar catabolism, oxidative stress, and auxin signaling were markedly upregulated in roots by FR light at 4 d post-grafting. FR0.3 (red/far-red ratio = 0.3) light significantly enhanced the expression of genes involved in hyperoxide scavenging (CmAPX1, CmPOD1, CmCAT1), sugar transportation (CmSWEET12, CmBST2, CmSCP1), and auxin response (CmAUX28, CmIAA11, CmSAUR20) compared with the control. Moreover, FR0.3 light treatment notably decreased reactive oxygen species content and improved antioxidant enzyme activities in roots compared with the control. However, despite increased gene expression, peroxidase and catalase did not contribute substantially to reactive oxygen species scavenging at the protein activity level under FR0.3 compared with other light qualities. In addition, sugar content and hexokinase activity responded differently to light quality: starch, sucrose, and hexokinase activity were significantly increased by FR0.3 light at 4 d post-grafting, while glucose content in the FR0.3 treatment was significantly higher than that in other treatments only at 8 d post-grafting. These results demonstrate that supplementary FR light significantly promotes rooting and growth of DRC grafted watermelon seedlings. Specifically, FR light can induce root regeneration in the rootstock, potentially by alleviating oxidative stress during grafting and providing a relatively stable plant environment through the synergistic effects of sugar metabolism, the antioxidant enzyme system, and auxin accumulation in the roots via the regulation of antioxidants, sugar metabolism, and auxin-related gene transcription. The findings from this study present a practical method to enhance the quality of grafted watermelon seedlings.